Ethyl 1-(2,4-dichlorobenzyl)-4-oxo-7-trifluoromethyl-1,4-dihydroquinoline-3-carboxylate - Hegde, Gurumurthy; Fun, Hoong-Kun; Loh, Wan-Sin; Shenvi, Seema; Isloor, Arun M. (International Union of Crystallography, 2012)
In the title compound, C20H22BrN5O22H2O, the Schiff base molecule exists in an E conformation with respect to the acyclic C N bond. An S(6) ring motif is formed via an intramolecular O—H N hydrogen bond. The dihedral angle between the imidazo[1,2-a]pyridine system and the benzene ring is 84.62 (5). In the crystal, N—H O, O—H O, O— H N, C—H O and C—H Br hydrogen bonds link the molecules into a three-dimensional network. The crystal packing is further stabilized by C—H and – interactions [centroid–centroid distance = 3.5365 (7) A ° ].